Subcutaneous abdominal adipose tissue is associated with an index of insulin sensitivity/resistance. (1st October 2016) - Niijima, Katsura; Shimoda, Yoko; Saito, Tsugumichi; Yamada, Eijiro; Niijima, Yawara; Okada, Shuichi; Yamada, Masanobu
ABSTRACT: To assess whether there is any clinical significance for determining the normal range of subcutaneous abdominal fat area, we compared fat area with insulin sensitivity. Visceral and subcutaneous abdominal fat area the L4-L5 thoracic level was determined by computed tomography (CT). Plasma glucose and insulin levels were determined after an overnight fast and calculated by the homeostatic model assessment of insulin resistance (HOMA-IR). We analyzed 350 (180 male and 170 female) subjects whose BMI was 18.5≤BMI<25. The subcutaneous abdominal fat area of the female subjects was 124.7 ± 46.13 cm 2 and that of male subjects was 77.53 ± 37.53 cm 2 (mean ± SD). We compared HOMA-IR between subjects whose visceral abdominal fat area was above 100 cm 2 and subcutaneous abdominal fat area below the mean + 2SD (15 subjects, 6 male and 9 female) with subjects whose visceral abdominal fat area was also above 100 cm 2 but whose subcutaneous abdominal fat area was above the mean + 2SD (20 subjects, 7 male and 13 female). The HOMA-IR of the former subjects group was 8.17+/−6.22 and that of the latter subjects group was 3.37+/−2.07 (p = 0.0486). Subjects with increased subcutaneous abdominal fat area displayed lower HOMA-IR values, demonstrating a protective effect of subcutaneous fat for individuals with visceral fat area above 100 2  cm.